Long Term Therapy of Cytomegalovirus Retinitis with Ganciclovir in a Child with Acquired Immunodeficiency Syndrome - Scott A Halperin; G Robert La Roche (Canadian Journal of Infectious Diseases)
Cytomegalovirus retinitis is the most severe ophthalmological complication of patients with acquired immune deficiency syndrome (aids). Ganciclovir must be given continuously to control progression of the disease or relapse typically occurs. Data in children are limited; this report describes a nine-year-old boy with transfusion-acquired aids who was treated with ganciclovir for 23 months for control of cytomegalovirus retinitis. The retinal disease was exacerbated when ganciclovir was temporarily withheld because of presumed drug toxicity, and improved with re-institution of therapy. When ganciclovir was finally discontinued because of complete loss of vision, the patient rapidly deteriorated and died; widespread cytomegalovirus infection was found at autopsy. Subcapsular cataracts appearing during therapy were thought to be a toxic effect of ganciclovir. Ganciclovir can be effective in controlling cytomegalovirus retinitis in children; however, similarities in laboratory findings may lead to confusion between systemic drug toxicity and disease progression.